ANALISIS FAKTOR-FAKTOR KESIAPAN DAN DUKUNGAN STAKEHOLDERS TERHADAP PERUBAHAN STATUS MENJADI BADAN LAYANAN UMUM DAERAH (STUDI PADA PUSKESMAS-PUSKESMAS DI KABUPATEN KLATEN) - Naniek Listyawati (ABIS: Accounting and Business Information Systems Journal, 2016)
This research is motivated by Letter of Minister of Domestic Affairs number 440/8130/SJ dated November 13th, 2013 on Optimizing the Implementation of National Health Insurance that describes the acceleration of puskesmas (community health center) change to Public Service Agency (Badan Layanan Umum Daerah/BLUD). Meanwhile, Klaten Regency Government has planned policy implementation of full BLUD for all puskesmas starting in 2017, while the results of BLUD readiness questionnaire show that only 41% puskesmas confirmed their readiness. This study aims to analyze the influencing factors of puskesmas readiness to change to BLUD and to determine the extent of supports from stakeholders and organizational commitment in implementing BLUD policy in Klaten Regency. The theory of organization change readiness by Weiner (2009) is used as research framework to assess the extent to which organization members appreciate the three determinants of implementation ability, namely task demands, resource availability, and situational factors. Research method implemented in this study is descriptive qualitative, with the data is collected through in-depth interviews with respondents who answering the questionnaire with "ready", "doubtful" and "not ready". The results of data analysis can be concluded that there are five factors that affect puskesmas readiness to transfer to BLUD, namely commitment to task demands, availability of resources, managerial skills of puskesmas head, regulatory preparedness, and stakeholders’ support in the implementation of changes into BLUD status. All stakeholders in Klaten Regency support this program and organizational commitment of puskesmas constructed by understanding the work and advantage of BLUD program to puskesmas.